Implementation of the 7 Habits of Great Indonesian Children at SMPS Islam Al Fadhila Demak - Fingkan Kumalasari; Ngabiyanto, Ngabiyanto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the implementation of the 7 Habits of Great Indonesian Children program and to identify its supporting and inhibiting factors within both the school and pesantren (Islamic boarding school) environments. The research employs a qualitative approach with descriptive analysis. Data collection techniques include interviews, observations, and documentation, conducted over a three-month period (May–July 2025) at SMPS Islam Al Fadhila and Pondok Pesantren Al Fadhila. Data analysis follows the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The research findings indicate that the 7 Habits—waking up early, worship, physical exercise, healthy and nutritious eating, enthusiasm for learning, community involvement, and going to bed early—are implemented in a structured and consistent manner. The synergy between the school and the pesantren plays a crucial role in embedding these habits into the students’ daily lives. The habits are incorporated through daily routines, character education programs, and collaborative efforts among educational stakeholders. Key supporting factors include the active engagement of school principals, teachers, pesantren administrators, and parents, along with the availability of facilities that support health and religious practices. These elements create an environment conducive to character development. However, several inhibiting factors were also identified. Among them are negative peer influences, lack of consistent role modeling from some junior pesantren staff, and occasional resistance from students adjusting to strict routines. This study contributes to a broader understanding of how holistic character education can be effectively integrated into dual educational systems (school and pesantren). The findings suggest the importance of consistency, collaboration, and environment in cultivating positive student behavior. It also provides a practical reference for educators seeking to implement similar programs in other Islamic educational institutions across Indonesia.